Ammonium Aminodiboranate: A Long‐Sought Isomer of Diammoniate of Diborane and Ammonia Borane Dimer. Issue 23 (26th April 2016) - Chen, Weidong; Yu, Haibo; Wu, Guotao; He, Teng; Li, Zhao; Guo, Zaiping; Liu, Huakun; Huang, Zhenguo; Chen, Ping
Abstract: Ammonium aminodiboranate ([NH4 ][BH3 NH2 BH3 ]) is a long‐sought isomer of diammoniate of diborane ([NH3 BH2 NH3 ][BH4 ]) and ammonia borane (NH3 BH3 ) dimer. Our results show that [NH4 ][BH3 NH2 BH3 ] is stable in tetrahydrofuran at −18 °C and decomposes rapidly to NH3 BH2 NH2 BH3 and H2 at elevated temperatures. The decomposition pathway is dictated by the dihydrogen bonding between H δ+ on NH4 + and H δ− on BH3, as confirmed by theoretical calculations. This is in contrast to the interconversion between [NH3 BH2 NH3 ][BH4 ] and (NH3 BH3 )2, although all three have dihydrogen bonds and the same stoichiometry. Abstract : At last ! Ammonium aminodiboranate ([NH4 ][BH3 NH2 BH3 ]), which is long sought for more than 90 years, is shown to be stable in tetrahydrofuran at −18 °C and decomposes rapidly to NH3 BH2 NH2 BH3 and H2 at elevated temperatures. The decomposition pathway is dictated by the dihydrogen bonding between H δ+ on NH4 + and H δ− on BH3, as confirmed by theoretical calculations and experimental results (see scheme). This is different to the interconversion between diammoniate of diborane ([NH3 BH2 NH3 ][BH4 ]) and ammonia borane (NH3 BH3 ).